2015
DOI: 10.1038/srep11519
|View full text |Cite
|
Sign up to set email alerts
|

High thermopower of mechanically stretched single-molecule junctions

Abstract: Metal-molecule-metal junction is a promising candidate for thermoelectric applications that utilizes quantum confinement effects in the chemically defined zero-dimensional atomic structure to achieve enhanced dimensionless figure of merit ZT. A key issue in this new class of thermoelectric nanomaterials is to clarify the sensitivity of thermoelectricity on the molecular junction configurations. Here we report simultaneous measurements of the thermoelectric voltage and conductance on Au-1,4-benzenedithiol (BDT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 35 publications
(60 reference statements)
0
43
0
Order By: Relevance
“…The tips on the electrodes surface become blunt after several break–reconnect processes (Figure d). An annealing process was further performed at 300 °C for 2 h. By this annealing process, the surface of the two quasi plane‐type electrodes was further smoothed due to the migration of metal atoms driven by the thermal excitation energy at the high temperature . In this way, a pair of atomic‐planar electrodes was obtained as shown in Figure e.…”
Section: Electrodes' Fabricationmentioning
confidence: 99%
See 1 more Smart Citation
“…The tips on the electrodes surface become blunt after several break–reconnect processes (Figure d). An annealing process was further performed at 300 °C for 2 h. By this annealing process, the surface of the two quasi plane‐type electrodes was further smoothed due to the migration of metal atoms driven by the thermal excitation energy at the high temperature . In this way, a pair of atomic‐planar electrodes was obtained as shown in Figure e.…”
Section: Electrodes' Fabricationmentioning
confidence: 99%
“…To elucidate the role of the atomic‐scale geometry of electrodes in determining the conductance of molecular devices and to find the optimized atomic‐scale geometries to improve the conductance of the molecular devices, we fabricated both atomic‐scale sharp (cone‐shaped) electrodes and atomic‐scale planar (plane‐shaped) electrodes employing mechanically controllable break junction (MCBJ) technique . We observed that the signal‐to‐noise ratio can be greatly improved with cone‐shaped electrodes, and we further observed that the conductance of the molecular junction with cone‐shaped electrodes can be 50% higher than the one with plane‐shaped electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…14,20 Incorporating a microheater structure into a nano-MCBJ facilitates the measurement of the Seebeck coefficient of SMJs, and it can also be used to examine whether the carriers flowing through an SMJ are holes or electrons. 23,24 Finally, the phases of molecular orbitals can be used to predict whether or not an electric current is flowing through an SMJ. 29 3.1 Single-Molecule Conductance Mechanism.…”
Section: Single-molecule Analysis Methodsmentioning
confidence: 99%
“…23 When the heater voltage was 3 V, the conductance and Seebeck coefficient of the single gold atom contacts were 1 G 0 (i.e., quantized conductance) and ΔV = 50¯V, respectively. The conductance and Seebeck coefficient of the SMJs were, conversely, approximately 1.0 © 10 ¹2 G 0 and about ΔV = ¹200 V, respectively.…”
Section: Bond Strength Between Electrodes Andmentioning
confidence: 99%
See 1 more Smart Citation